Wealth and Asset Holdings of Immigrants in Germany - Mathias Sinning (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper examines the relative wealth position and the portfolio choices of immigrants in Germany. The empirical findings reveal significant differences in overall wealth and various wealth components between German natives and immigrants. Differences in real estate constitute the major part of different levels of net worth, indicating that disparities in home-ownership rates are responsible for the main part of the overall wealth gap. Moreover, migrants' degree of portfolio diversification is significantly lower than that of comparable natives. The results of a decomposition analysis suggest that differences in wealth and asset holdings may be explained by disparity in educational attainment to a sizable extent, while the effects of income differentials and differences in demographic characteristics are insignificant.
Keywords: F22; D31; 330; International migration; wealth accumulation; decomposition analysis; multiple imputation